Studying innovation ecosystems using ecology theory - Shaw, Duncan R.; Allen, Tim (Elsevier, 2016)
This paper proposes a set of perspectives for studying innovation ecosystems that are based on ecological research. Our perspectives are based on fundamental similarities between natural and business systems. We suggest that innovation ecosystems can be defined as pathways of interlinked business models. Pathways are characterised by the flows they convey not the types of business model that support the flows. These pathways convey material and informational resources, as well as value. Like the nutrient and energy pathways in natural ecosystems. Pathways help to recycle scarce resources such as customer attention and customer-derived information. Business model descriptions are similar to an organism’s genome in that they describe limitations on sensing, acting and understanding. We conceptualise this as the ‘umwelt’; the self-world. These limitations have implications for how firms and customers interact with customers. They have other implications for how firms interact with each other in business model communities and how they accommodate each other. We illustrate and test these ecological perspectives using a case study of a healthcare smartphone app’s ecosystem. We find that our perspectives can be used as novel methods of studying interactions between business models; or to study ecosystem building.